Anatomy of north- western Himalayan leopard - ., Archana; Sharma, D N; Rajput, Rajesh; Kishtwaria, R S; Bhardwaj, R L; Sudhakar, L S (The Indian Journal of Animal Sciences, 2011)
Anatomy of north-western Himalayan leopard was studied. The leopard specimen measured (cranio-caudal axis length) 176 cm. Head height, osseous thoracic cage, thyroid gland, trachea, weight of lungs, thoracic aorata, abdominal cavity, weight of stomach, length of intestines, different measurements ofspleen, liver were also reported.